New Approach of Highly Efficient Fermentation Process for Bio ethanol using Xylose as Agricultur e Residues - Abu Saleh Ahmed; Seiya Watanabe; Sinin Hamdan; Tsutomu Kodaki; Keisuke Makino (ASEAN Journal on Science and Technology for Development, 2010)
Agricultural waste biomasshas already been transferred to bioethanol and used as energy related products, although many issues such as efficiency and productivity still exist to be overcome. In this study, the protein engineering was applied to generate enzymes with completely reversed coenzyme specificity and developed recombinant yeasts containing those engineered enzymes for construction of an efficient biomass-ethanol conversion system. Recombinant yeasts were constructed with the genes encoding a wild type xylose reductase (XR)and the protein engineered xylitol dehydrogenase (XDH)(with NADP) of Pichiastipitis. These recombinant yeasts were characterized based on the enzyme activity and fermentation ability of xylose to ethanol. The protein engineered enzymes were expressed significantly in Saccharomycescerevisiaeas judged by the enzyme activity in vitro. Ethanol fermentation was measured in batch culture under anaerobic conditions. The significant enhancement was found in Y-ARSstrain, in which NADP+-dependentXDH was expressed; 85% decrease of unfavorable xylitol excretion with 26% increased ethanol production, when compared with the reference strain expressing the wild–type XDH.